Global health security: the wider lessons from the west African Ebola virus disease epidemic. Issue 9980 (9th May 2015) - Heymann, David L; Chen, Lincoln; Takemi, Keizo; Fidler, David P; Tappero, Jordan W; Thomas, Mathew J; Kenyon, Thomas A; Frieden, Thomas R; Yach, Derek; Nishtar, Sania; Kalache, Alex; Olliaro, Piero L; et al.
Summary: The Ebola virus disease outbreak in West Africa was unprecedented in both its scale and impact. Out of this human calamity has come renewed attention to global health security—its definition, meaning, and the practical implications for programmes and policy. For example, how does a government begin to strengthen its core public health capacities, as demanded by the International Health Regulations? What counts as a global health security concern? In the context of the governance of global health, including WHO reform, it will be important to distil lessons learned from the Ebola outbreak. The Lancet invited a group of respected global health practitioners to reflect on these lessons, to explore the idea of global health security, and to offer suggestions for next steps. Their contributions describe some of the major threats to individual and collective human health, as well as the values and recommendations that should be considered to counteract such threats in the future. Many different perspectives are proposed. Their common goal is a more sustainable and resilient society for human health and wellbeing.